Phase and morphology evolution of corundum-type Ni4Nb2O9powders synthesized by solid-state reaction - O. Khamman (2018)
The solid-state mixed oxide method via a rapid vibro-milling technique is explored in the preparation of single-phase nickel diniobate (Ni4Nb2O9) powders. The formation of the Ni4Nb2O9phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM and EDX techniques. It has been found that minor phases of unreacted NiO and Nb2O5precursors and NiNb2O6phase tend to form together with the Ni4Nb2O9phase, depending on calcination conditions. It is seen that optimization of calcination conditions can lead to a single-phase Ni4Nb2O9in an orthorhombic phase. © 2006 Elsevier B.V. All rights reserved.